Thermoluminescence and photoluminescence analyses of MEH-PPV, MDMO-PPV and RU(bpy)3 gamma-irradiated polymer thin films. (August 2015) - Ortiz-Morales, A.; Ortiz-Lopez, J.; Cruz-Zaragoza, E.; Gómez-Aguilar, R.
Abstract: Effects of irradiation with 60 Co gamma photons on poly[2-methoxy-5-(2-ethylhexyloxy)-1, 4-phenylenevinylene] (MEH-PPV), poly[2-methoxy-5-(3′, 7′ dimethyloctyloxy)-1, 4-phenylenevinylene] (MDMO-PPV) and tris(2, 2′-bipyridyl)dichlororuthenium(II) hexahydrate (Ru(bpy)3 ) thin films were analyzed regarding their thermoluminescence (TL) and photoluminescence (PL) properties. A linear TL dose response was obtained from the MEH-PPV and MDMO-PPV polymer films in dose ranges of approximately 0.170–4.08 kGy and 0.170–0.850 kGy, respectively, followed by a supralinear behavior. A dependence on the conjugation length of the polymer chains which was favored by heating of the film, was observed, and irradiation generated a blue-shift in MEH-PPV and Ru(bpy)3 . Furthermore, the PL structure was not modified. The most likely effect involved in the TL emission was trapping. The high activation energy values of the traps in the TL may be attributed in part to the binding energy of the exciton. A deconvolution process was carried out to obtain the kinetic parameters from the TL glow curves and PL spectra. Highlights: Irradiation effects on MEH-PPV, MDMO-PPV and Ru(bpy)3 were analyzed by TL and PL. The dose response of PPV derivatives was linear at higher doses (0.170–4.08 kGy). Activation energy, was larger than 2 eV, suggest a possible good stability of traps. PL spectra for non-irradiated and gamma irradiated polymer are almost identical.